Local thermal non-equilibrium approach on entropy and thermal features of buoyancy-driven flow of nano-encapsulated PCMs suspension: role of geometrical parameters - Ohid, S.A.; Nayak, Manoj Kumar; Ali, Rifaqat; Galal, Ahmed M. (International journal of numerical methods for heat & fluid flow, 2025)
Purpose Nano-encapsulated phase change materials (NEPCMs) are favourable in terms of their potentials to ameliorate the efficiency of working liquids, keeping the apparatus at a determined cooling temperature. NEPCMs are used in thermal management of buildings, air-conditioning systems and electronic cooling devices. Because of notable temperature disparity among two components (solid as well as nanofluid) in linear/non-linear porous material, an interface model such as local thermal non-equilibrium (LTNE) is highly applicable in electronic equipment, geothermal engineering and high-conductivity foams. Forchheimer-Brinkman-extended Darcy model (FBEDM) featured with fluid flow at higher velocities in high porosity porous medium is significantly found in solar thermal systems, heat exchangers and condensation and boiling operations. In view of above real-world applications of NEPCMs, LTNE and FBEDM, the aim of this work is to scrutinize the effect of LTNE on hydrothermal features of buoyancy-driven flow of NEPCMs suspension in an inclined square chamber subject to FBEDM. The introduction of the mechanism of horizontal displacement and vertical displacement (VD) of channels subject to inclined domain, FBEDM and LTNE is the novelty of this work. Design/methodology/approach The equations govern this problem are solved via finite element method and irreversibility in the two components (nanofluid and solid) of the porous structure is also explored. Findings The important findings of this study are that mean Nusselt numbers in nanofluid and porous matrix phases peter out by 15.71% and 29.6% with rise of VD from 0.3–0.6 while those whittle down by 23.73% and 44.12% with rise of HD from 0.3–0.7. Average Bejan number reduces by 8.69% and 0.93% with amplification of cavity inclination angle (a) from 0° to 30° and from 30° to 60° while it enhances by 3.79% with increase of a from 60° to 90°. Originality/value Although there are some theoretical and experimental studies on NC of nano-encapsulated PCMs, there exist limited studies on the NC of NEPCMs subject to LTNE and FBEDM altogether in which geometrical parameters’ roles have been analyzed. This work is the first to examine the influence of HD, VD and cavity inclination angle (a) on the entropy and hydrothermal specifications of buoyancy-driven flow of NEPCMs suspension in an inclined square chamber featured with LTNE and FBEDM.